2007
DOI: 10.1007/s00441-006-0377-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphofunctional changes in Leydig cells throughout the continuous spermatogenesis of the freshwater teleost fish, Serrasalmus spilopleura (Characiformes, Characidae): an ultrastructural and enzyme study

Abstract: The freshwater fish Serrasalmus spilopleura (piranha) has a continuous type of reproduction; gametes are constantly produced and released during the reproductive cycle. The testes do not undergo seasonal morphological changes but exhibit two constant regions throughout the year: the medullar region (involved with spermatogenesis) and the cortical region (involved with spermiation and sperm storage). We have evaluated the ultrastructure of the Leydig cells and the activity of 3beta-HSD (an essential enzyme rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…The testicular parenchyma of G. carapo displayed the germinal and interstitial compartments described in all vertebrates. As in other teleost fish (Nobrega and Quagio‐Grassiotto, ; Vazquez et al, ), the seminiferous tubules of this species contained spermatogenic cysts formed by Sertoli cells that envelop a group of synchronously developing germ cells. Histologically, the testis of G. carapo seem to correspond to the unrestricted spermatogonial testicular type, found in most teleosts, where spermatogonia reside along the testicular tubules (Grier et al, ; Grier, ).…”
Section: Discussionsupporting
confidence: 61%
“…The testicular parenchyma of G. carapo displayed the germinal and interstitial compartments described in all vertebrates. As in other teleost fish (Nobrega and Quagio‐Grassiotto, ; Vazquez et al, ), the seminiferous tubules of this species contained spermatogenic cysts formed by Sertoli cells that envelop a group of synchronously developing germ cells. Histologically, the testis of G. carapo seem to correspond to the unrestricted spermatogonial testicular type, found in most teleosts, where spermatogonia reside along the testicular tubules (Grier et al, ; Grier, ).…”
Section: Discussionsupporting
confidence: 61%
“…The number of steroid-producing LC is positively correlated with spermatogenesis in teleost fish (Kanamori et al 1985, Loir et al 1989, Nobrega & Quagio-Grassiotto 2007. We demonstrated that stable d-males had testes with large groups of LC.…”
Section: Histological and Gene Expression Studies Give Evidence For Dmentioning
confidence: 50%
“…1995; Miura and Miura 2003), the seminiferous tubules and lobules are composed of cysts of spermatogenic cells that are delimited by cytoplasmic projections of the Sertoli cells. As in other teleosts, the Leydig cells of all species studied herein are located in the interstitial compartment of the testis, isolated or in groups, near blood vessels (Nóbrega and Quagio‐Grassiotto 2007).…”
Section: Discussionmentioning
confidence: 67%